The association of serum hsa-miR-21-5p expression with the severity and prognosis of heart failure with reduced ejection fraction - Lingmiao Wang; Ailin Guo; Shuang Liang; Lingling Yu; Bai Shen; Zhihang Huang (BMC Cardiovascular Disorders)
Abstract Background Heart failure poses a huge burden on the global population, and approximately 50% cases have reduced ejection fraction, namely, heart failure with reduced ejection fraction (HFrEF). The research was supposed to explore the relationship between serum hsa-miR-21-5p expression and the severity/prognosis of HFrEF. Methods A retrospective analysis was conducted on 105 HFrEF patients and 86 healthy volunteers. RT-qPCR was used for the detection of serum hsa-miR-21-5p levels. Whether serum hsa-miR-21-5p expression correlated to cardiac function and hemodynamic indicators was evaluated using Spearman correlation analysis. Receiver operating characteristic and Kaplan-Meier analyses were implemented to evaluate the predictive significance of serum hsa-miR-21-5p for cardiovascular re-hospitalization and cardiovascular deaths in HFrEF patients. Independent risk factors for cardiovascular deaths were analyzed based on COX regression. Results Higher heart rate, fasting plasma glucose (FPG), N-terminal pro-brain natriuretic peptide (NT-pro-BNP), left atrial diameter (LAD), systolic pulmonary artery pressure (sPAP), pulmonary vascular resistance (PVR), pulmonary capillary wedge pressure (PCWP), and hsa-miR-21-5p as well as lower left ventricular ejection fraction (LVEF) and left ventricular fractional shortening (LVFS) were detected in the HFrEF patients than in the controls. Hsa-miR-21-5p expression increased in HFrEF patients with the increase of NYHA grade. Serum hsa-miR-21-5p expression in HFrEF patients was positively relevant to NT-pro-BNP, LAD, sPAP, PVR, and PCWP but negatively related to LVEF and LVFS. Serum hsa-miR-21-5p had a high predictive value for cardiovascular re-hospitalization and cardiovascular deaths in HFrEF patients. High hsa-miR-21-5p expression was an independent dangerous factor for cardiovascular deaths. Conclusion Collectively, hsa-miR-21-5p expression in HFrEF patients is correlated with disease severity and the risk of cardiovascular re-hospitalization and cardiovascular deaths in HFrEF patients, indicating a new direction for evaluating the disease situation and prognosis.